Memories of time past. - Lottman, Herbert (Bookseller, 2006)
The article focuses on the views of the author on the publishing company Gallimard. At the recent Bologna Children's Book Fair, the author hardly recognized a soul on the stands of leading publishers. The author remembered when Pierre Marchand, a sailor at heart, and a self-taught publisher, revitalized the weary Gallimard logo with a new generation of children's books, making children's nonfiction at least as entertaining as stories, and perhaps more useful. Gallimard, which hasn't been number one in adult books for a long lime, is definitely number one for French children.